DiverCIAT - Genowefa Blundo Canto, Impact Assessment Post Doc - International Center for Tropical Agriculture (2016)
CIAT Impact Assessment Post Doc Genowefa Blundo Canto discusses growing up in a Polish and Italian family and how that led her to a career in international development.